Pengaruh Kepemimpinan Transaksional Terhadap Kinerja dengan Variabel Kepuasan Kerja Sebagai Variabel Intervening (Studi Pada Staf Pengajar Politeknik Negeri Sriwijaya) - Paisal Paisal (Program Studi Magister Manajemen FE Unsri, 2011)
This study aimed to know the impact of transactional leadership on performance with variable job satisfaction as an intervening variable. From the results of testing using path analysis techniques, the results of this study showed that transactional leadership has a significant, directly or indirectly to the performance. Significantly influence job satisfaction directly to performance. Transactional leadership which has been already applied in the Polytechnic of Sriwijaya could increase job satisfaction and performance. Polytechnic of Sriwijaya needs to improve employee satisfaction, this includes the satisfaction of salary or wages, the work itself, the leadership of co-workers or superiors, promotion and working environment/organization. This is because employees' job satisfaction have a significant and positive impact on the performance of teaching staff. Polytechnic leaders need to provide the opportunity or the greatest possible freedom to the teaching staff to improve motivation, ability, ideas and develop its own potential. Having the opportunity or freedom can create and support positive development of all business activities of employees in order to generate performance.Keywords: Transactional leadership, Job satisfaction, Performance.